2021
DOI: 10.1186/s40738-021-00097-4
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of extensive placenta accreta in twin pregnancy after GnRH agonist treatment of adenomyosis

Abstract: Background Adenomyosis remains an enigma for the reproductive endocrinologist. It is thought to contribute to sub-fertility, and its only curative treatment is hysterectomy. However, studies have documented increased live birth rates in women with adenomyosis who were treated with gonadotropin releasing hormone agonist (GnRHa). Case Here we present a case of a 52-year-old woman with adenomyosis who had three failed frozen embryo transfers (FETs) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The severity of adenomyosis was also unknown, that is, whether adenomyosis was diffuse or focal, and there may be missed cases of asymptomatic adenomyosis in the control group resulting in possible misclassification. Prior treatments for adenomyosis were not also captured in this dataset, and it has been suggested that treatments such as GnRH‐agonists may increase the risk for placental pathology 25 . Prior uterine curettage was also not assessable due to lack of specific codes, but this could be a possible unmeasured confounder for abnormal placentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of adenomyosis was also unknown, that is, whether adenomyosis was diffuse or focal, and there may be missed cases of asymptomatic adenomyosis in the control group resulting in possible misclassification. Prior treatments for adenomyosis were not also captured in this dataset, and it has been suggested that treatments such as GnRH‐agonists may increase the risk for placental pathology 25 . Prior uterine curettage was also not assessable due to lack of specific codes, but this could be a possible unmeasured confounder for abnormal placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior treatments for adenomyosis were not also captured in this dataset, and it has been suggested that treatments such as GnRH‐agonists may increase the risk for placental pathology. 25 Prior uterine curettage was also not assessable due to lack of specific codes, but this could be a possible unmeasured confounder for abnormal placentation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, according to a study of 45 subjects, triptorelin with add-back therapy may be beneficial to infertile patients irrespective of IVF, by reducing uterine size and enhancing elasticity, hence facilitating spontaneous pregnancy [ 85 ]. Several case reports have further demonstrated effectiveness in patients with severe adenomyosis suffering from secondary infertility [ 86 , 87 , 88 ]. One of these women later presented with severe pregnancy complications due to insufficiently decidualized endometrium, but it was not clear whether this event was related to the effect of GnRH agonist [ 88 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%
“…Several case reports have further demonstrated effectiveness in patients with severe adenomyosis suffering from secondary infertility [ 86 , 87 , 88 ]. One of these women later presented with severe pregnancy complications due to insufficiently decidualized endometrium, but it was not clear whether this event was related to the effect of GnRH agonist [ 88 ]. Niu et al reported a significant improvement in rates of clinical pregnancy, successful implantation, and ongoing pregnancy in 339 infertile patients with adenomyosis undergoing treatment with GnRH agonist prior to frozen embryo transfer [ 48 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%